Unveiling the Pathways to Sustainable Lobster Industry Development: A Comprehensive Case Study of Sawarna Village, Banten Province - Diajeng Reztrianti; Mishelei Loen; Achmad Sulistyono (Ilomata International Journal of Social Science, 2023)
This research aims to analyze the challenges in implementing sustainable business practices at Lobstamasta, a lobster industry company in Sawarna village, Banten. This research uses a qualitative method approach by interview to analyze the challenges in implementing sustainable business practices at Lobstamasta. The interview method is used to obtain an in-depth understanding of stakeholders, while questionnaires are used to collect large amounts of data. The findings of this research show that there are various main obstacles, including lack of commitment, limited resources, and limited understanding. The implication of this research is the need for corrective measures, such as increasing employee awareness through education, better allocation of financial resources, and strengthening sustainability policies. Close collaboration between government, entrepreneurs and communities is also needed to create an environment that supports and accelerates the process of sustainable lobster cultivation, with a positive impact on the local economy and environment. Implications of this research include: 1) Improved Awareness and Education: Increasing employee awareness and understanding through education and training programs can increase commitment to sustainable practices; 2) Optimizing Financial Resource Allocation: Implementing wiser financial resource allocation strategies to support investments in sustainable technology and equipment; and 3) Government-Entrepreneur-Community Collaboration: Close collaboration between government, entrepreneurs and society is important to create support and implementation of sustainable practices.